Process of effectiveness of accelerated experiential dynamic psychotherapy - S. Mohammad; A. Jazayeri; B. Dowlatshahi; O. Rezaei; A. PourShahbaz (Afarand Scholarly Publishing Institute, 2009)
Objectives : Regarding to importance of Dynamic Psychotherapies in treatment of psychiatric disorders, especially their increased development in recent years the purpose of this study was to investigate the efficacy of one kind of short term dynamic psychotherapy called Accelerated Experiential Dynamic Psychotherapy (AEDP) on major depression and the role of classic and tactical defense mechanisms (as mediators) in the process of change.     Materials & Methods : Current study is a single subject design with a sample size of six patients (2 male, 4 female). Interventions are arranged based on multiple baselines, across subject design. Patients were on average 28 years old . All patients were diagnosed with major depression in two separate interviews by a psychiatrist for a preliminary evaluating axis I & II and through using the SCID by researcher for implement inclusion /exclusion criteria accurately. Analysis was carried out visually and with non parametric ANOVA (friedman).   Results: analysis of data demonstrated that, scores of depression (BDI) and social adjustment (SAS) were significantly different in three phases of pre, during and post treatment. Also there was significant difference between average scores of tactical defense mechanisms in these phases. But there were no difference between average scores of classical defense mechanisms in these phases.   Conclusion: AEDP was significantly effective in reducing depression symptoms and using tactical defense mechanisms .but AEDP was not effective on classic defense mechanisms in 20 therapeutic sessions.